2006
DOI: 10.1097/01.brs.0000215048.51237.3c
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Local Bone Versus Autogenous Iliac Crest Bone Graft in the Instrumented Posterolateral Fusion of the Lumbar Spine

Abstract: Use of local bone graft alone achieved a similar fusion rate in single-level fusion but a much smaller fusion rate in multilevel fusion compared with the ICBG group. Local bone graft alone achieved a similar clinical outcome but less morbidity irrespective of number of fusion level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
112
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 14 publications
2
112
1
2
Order By: Relevance
“…There has been one report comparing the clinical and radiologic outcome of instrumented posterolateral lumbar fusion using local bone versus an autogenous ICBG using a retrospective comparative study [9]. Overall fusion rate was higher in the ICBG group (75%) compared with the local bone graft group (65%), but not significantly different [9]. In the current prospective randomized study, fusion rate using local bone graft and ICBG was consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…There has been one report comparing the clinical and radiologic outcome of instrumented posterolateral lumbar fusion using local bone versus an autogenous ICBG using a retrospective comparative study [9]. Overall fusion rate was higher in the ICBG group (75%) compared with the local bone graft group (65%), but not significantly different [9]. In the current prospective randomized study, fusion rate using local bone graft and ICBG was consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…Prospective studies evaluating fusion rate using instrumented posterolateral fusion with ICBG showed results from 82 to 95% [2,12]. There has been one report comparing the clinical and radiologic outcome of instrumented posterolateral lumbar fusion using local bone versus an autogenous ICBG using a retrospective comparative study [9]. Overall fusion rate was higher in the ICBG group (75%) compared with the local bone graft group (65%), but not significantly different [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations